Penerapan Asesmen Diagnostik Kognitif dalam Pembelajaran Mencipta Puisi di SMP Kelas VIII (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study discusses the implementation of cognitive diagnostic assessment in poetry writing instruction for eighth-grade students at the junior high school level. The cognitive diagnostic assessment is conducted prior to the learning activities to measure students' cognitive readiness regarding the material to be taught. This study employs a qualitative method with a descriptive approach, aiming to explain the reality based on existing data and to describe how cognitive diagnostic assessment is applied in school-based instruction. This type of assessment is formative in nature and is intended to assist educators in designing instructional strategies that align with the conditions and abilities of the students. The assessment instruments used include multiple-choice and essay questions, which are designed to measure students’ prior knowledge as well as their thinking and expressive abilities in composing poetry. The assessment results show that the majority of students, 14 out of 22 participants, fall into the